(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Today, oil and gas are important pillars of the global energy sector. All resources used in our daily lives are directly or indirectly linked to the oil and gas industry. The oil and gas industry is an important necessity for global economic growth. The economic growth of any country is linked to the size of its demand for energy, and with the increasing demand for energy and the development of its alternatives (renewable energy), oil and gas will continue to meet the world’s needs in the coming years as it is one of the largest sectors in the world, especially the manufacturing industries.